A comprehensive phytochemical and pharmacological review on sesquiterpenes from the genus Ambrosia. Issue 7 (July 2022) - Kovács, Balázs; Hohmann, Judit; Csupor-Löffler, Boglárka; Kiss, Tivadar; Csupor, Dezső
Abstract: Sesquiterpenes are bitter secondary metabolites characteristic to the genus Ambrosia (Asteraceae) and constitute one of the most diverse classes of terpenoids. These compounds exhibit broad-spectrum bioactivities, such as antiproliferative, cytotoxic, antimicrobial, anti-inflammatory, molluscicidal, schistomicidal, larvicidal, and antiprotozoal activities. This review compiles and discusses the chemistry and pharmacology of sesquiterpenes of the Ambrosia species covering the period between 1950 and 2021. The review identified 158 sesquiterpenes previously isolated from 23 different Ambrosia species collected from across the American, African, and Asian continents. These compounds have guaiane, pseudoguaiane, seco-pseudoguaiane, daucane, germacrane, eudesmane, oplopane, clavane, and aromadendrane carbon skeletons. Most sesquiterpene compounds predominantly harbor the pseudoguaiane skeleton, whereas the eudesmanes have the most varied substituents. Antiproliferative and antiprotozoal activities are the most promising bioactivities of sesquiterpenes in Ambrosia and could lead to new pathways toward drug discovery. Abstract : Ambrosia, Antiproliferative activity, Antiprotozoal activity, Biological activities, Sesquiterpenes.